Pendidikan Pranatal dalam Perspektif Al-Qur’an - Aridlah Sendy Robikhah (Al-Mada: Jurnal Agama, Sosial, dan Budaya, 2022)
For parents, having children is a great gift and trust from Allah SWT. Therefore, parents have a responsibility to educate optimally. According to the Qur'an, providing education to the Qur'an can be done since the child is still in the womb, which can be called prenatal education. So the purpose of writing this article is to examine some verses of the Qur'an that explain prenatal education. So that this article can be used as a reference for prospective parents to prepare the next generation of the nation with good morals and intelligence. This article uses a literature study; the author explores the verses of the Qur'an and several scientific references related to prenatal education. As a result of this research, some prenatal education that parents can do includes praying for the child's good, maintaining the mother's condition by providing good and halal food intake, and providing education about worship by inviting children to worship with the mother. Providing this kind of stimulation can be a separate education for the fetus in the womb.